Reflective Learning in Higher Education - Colomer Feliu, Jordi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book on 'Cooperative Learning in Higher Education' addresses the development of both reflective teaching and learning in higher education to promote sustainable education in several disciplines where reflection is at the core of sustainable development. The book explores reflection within higher education and/or within instructional approaches to higher education, not only via in-house and external individuals, collective initiatives and activities that focus on reflection and the generation of knowledge, but also on the transformative outputs of learning communities. We place an emphasis on reflective practices and communities, as well as linking reflective learning and the development of professional identity through reflection. The book also addresses the connections between theoretical and applied research on reflective practices and knowledge generation in all areas, as well as professional practice and identity through theoretical definitions, situated and grounded practice, and transformative knowledge.